(untitled) (Bangladesh Renal Journal, 2026)
Background: Recurrent intradialytic hypotension (rIDH) happens quite often and can be a significant issue for patients with End-Stage Renal Disease (ESRD) undergoing hemodialysis (HD). We know how it affects them in the short term, but we really need to look deeper into how it impacts both their physical and mental well-being in a community setting. Objectives: To determine the prevalence of rIDH and assess its effects on the physical and mental health outcomes of ESRD patients undergoing maintenance HD. Methods: We carried out a study at a community medical college in Bangladesh from January to July 2025. We focused on a specific group of 103 adult patients with end-stage renal disease (ESRD) who were on regular hemodialysis. We defined resistant intradialytic hypotension (rIDH) as having a lowest systolic blood pressure below 90 mmHg during at least 30% of their dialysis sessions over a month. To gather data, we used a structured questionnaire and the SF-36 health survey to evaluate health-related quality of life, along with information from hospital records for clinical details. For the analysis, we utilized SPSS software version 25.0. Results: We found that recurrent IDH was fairly common, affecting about 38.8% of the 40 patients we looked at. Those with rIDH tended to be older, had been on dialysis for longer, and had more health issues overall (p<0.05). They also reported significantly more negative symptoms, like cramping—72.5% compared to just 19.0% in others (p<0.001). Plus, the SF-36 scores showed that their quality of life was really suffering, with scores much lower in both physical and mental health areas (p<0.001). Conclusion: Recurrent low blood pressure during dialysis is really common and can take a toll on both the physical and mental well-being of patients undergoing hemodialysis. It’s really important to put proactive management strategies in place to enhance their overall quality of life and improve clinical results for these patients. Bang. Renal J. 2026; 8(2): 51-55